Globalization & Regionalization in International Trade - Ramona Frunza; Liviu George Maha; Claudiu Gabriel Mursa (CES Working Papers, 2009)
The concept of globalization refers to the growing interdependence of countries, resulting from the increasing integration of trade, finance, investments, labor markets and ideas in one globalmarketplace. The most important elements of this process are the international trade and the cross-border investment flows. Economic globalization has increased the specialization of workers, while the companies compete in global markets. Even globalization has recently become a common topic in academic discourse, many economists focused, from the 1980s and 1990s, in addition to globalization, on regionalization - the growth of networks of interdependence within multinational regions of the world. The recent decades arecharacterized by the fact that the world trade grew faster than world output, which implies that an increasing share of world GDP crosses international borders. The trend is explained, mostly, by thesubstantially declining of the trade barriers during the same period, as a result of successive trade negotiation rounds under the auspices of the GATT/WTO, unilateral trade liberalization and regional tradeagreements. Even there are global connections between all the countries, the strongest political and economic integration is being created within a few specific regions of the world: Europe, North America and East Asia.
Keywords: 330; globalization; regionalization; international trade; trade agreement; trade liberalization; economic integration; global market